Age-dependent overall survival benefit of androgen deprivation therapy for metastatic prostate cancer. (December 2019) - Keating, Matthew J; Giscombe, Lisa; Tannous, Toufic; Reddy, Nishitha; Mukkamalla, Shiva Kumar R; DeSouza, Andre; Rathore, Ritesh
Background: Androgen deprivation therapy (ADT) remains a standard of care in metastatic prostate cancer. Recent prospective trials have explored addition of chemotherapy to ADT. We retrospectively examined overall survival in metastatic prostate cancer patients treated with ADT, chemotherapy plus ADT (C + ADT), or observation from 2004 to 2010 using National Cancer Database data. Methods: Using the National Cancer Database, 21, 977 patients with metastatic prostate cancer diagnosed from 2004 to 2010 were identified. Multivariate logistic regression, Kaplan-Meier survival analysis and Cox proportional hazards regression modeling were implemented, with overall survival as the primary endpoint. Results: Five-year overall survival was 13.6% in patients aged ≥ 75 years vs. 30.1% (age 65–74) and 34.5% (age 18–64). Subgroup analysis of age-based cohorts (<65 and ≥65 years) showed poor overall survival for C + ADT vs. ADT alone, both in younger (HR 1.35, 95% CI 1.21–1.50; p < 0.0001) as well as older (HR 1.21, 95% CI 1.08–1.34; p = 0.0006) populations. Younger patients had no significant difference in overall survival for observation vs. ADT (HR 0.99, 95% CI 0.92–1.08; p = 0.9121). Besides age, other factors impacting overall survival included race, rural/urban settings, comorbidity score, income, PSA and radiation. Discussion: Younger patients had no significant difference in overall survival between observation or ADT. This implies a group of younger patients in whom ADT does not confer any overall survival benefit. Future clinical trials with genetic and biologic markers are needed to delineate which subgroups would not benefit from C + ADT or ADT alone. This is of utmost clinical importance given the negative impact of ADT on quality of life and comorbidities.